The relationship between mindfulness, anxiety and depression during the COVID-19 pandemic: A meta-analysis of correlational studies - Xu, Fuming; Zhu, Wanling; Chen, Qian; Tang, Youmei (Frontiers in Psychology, 2023)
Background：The emergence of the COVID-19 pandemic has created an environment in which numerous determinants of poor mental health are intensified. Lockdown, re-lockdown, and media coverage of the spread of the virus, have the potential to contribute to increased levels of anxiety and depression. Mindfulness may act as a buffer against COVID-19-related depressive and anxiety disorders. Methods: We conducted a systematic review and meta-analysis by searching PubMed, PsycINFO, Web of Science, and Google Scholar for any study published between January 2020 and March 2022. In this study, Comprehensive Meta-Analysis Version 3.3 software was applied to evaluate the effect size by random effect model. In addition, the heterogeneity analysis was evaluated using indicators Q and I2 indicators. Three methods were used to test for publication bias: funnel plot, Classic Fail-safe N, and Egger's linear regression. According to the features of the included articles, subgroup analysis was utilized for the moderator analysis of this study. Results: The analysis finally included 12 articles (16 samples, N=10,940) and obtained 26 independent effect sizes. In accordance with the meta-analysis, in the random effect model, the correlation between mindfulness and anxiety was -0.330 (p<0.001), and the correlation between mindfulness and depression was -0.353 (p<0.001), which supported the effect of mindfulness on anxiety and depression. In the meta-analysis of the correlation between mindfulness and anxiety, study region had an essential moderating effect (p<0.001). The Sample type did not produce a significant moderating effect (p=0.190). The mode of action of mindfulness was a significant moderator(p=0.038). In the meta-analysis of the linkage between mindfulness and depression, regional differences had a significant moderating effect (p<0.001). The sample type had no discernible moderating impact (p=0.213). The mode of action of mindfulness was a significant moderator (p=0.003). Conclusions: Our meta-analysis indicated that there was an essential correlation between public mindfulness and mental health. Our systematic review added evidence supporting the beneficial nature of mindfulness. A cascading development of beneficial traits that improve mental health may start with mindfulness.